A Model for Sustainable Development in Higher Education: Heliopolis University for Sustainable Development in Egypt - Elyse Van Peel; Ahmed Elshazly (Universitas Diponegoro, 2025)
Sustainable development ensures future generations can meet their needs, making it vital for institutions to adopt sustainable practices. The UN’s 17 Sustainable Development Goals (SDGs) offer a framework to tackle global challenges, with universities playing a key role through research, education, and partnerships. While studies have explored SDGs in Higher Education Institutions (HEIs), a comprehensive, institution-wide approach remains underexamined, particularly in the Middle East North African region. This study addresses that gap by analyzing SDG integration at Heliopolis University for Sustainable Development (HUSD) in Egypt. Established in 2012, HUSD embeds sustainability across academic and operational dimensions, aligning with SEKEM—a holistic sustainable development initiative in the Middle East—and its localized framework, the Sekem Vision Goals (SVGs). The case study examines SDGs across education, research, governance and community engagement, and using content analysis of curricula and journal publications. An UNESCWA-made survey assesses faculty and student perceptions, while thematic analysis highlights key priorities at HUSD, showing its attention to a holistic approach, community-building efforts, and the climate impact of university-led projects. By showcasing best practices for comprehensive SDG implementation, this study provides valuable insights for HEIs, particularly in the Global South, to integrate sustainability into their structures and enhance their global contributions